1998
DOI: 10.1111/j.1574-695x.1998.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor characterization of antigenic site A of foot-and-mouth disease virus presented in different vector systems

Abstract: The region 141-160 of the VP1 protein of foot-and-mouth disease virus known as site A is an immunodominant region that has been extensively studied for the purpose of developing a synthetic vaccine. In the present study, site A of foot-and-mouth disease virus was inserted in three different loops of the maltose-binding protein and its antigenicity was compared with site A presented as a conjugated synthetic peptide or inserted in beta-galactosidase. The affinity of antibodies elicited against the site A synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We previously showed that multiple insertions of a major FMDV B-cell epitope from the VP1 capsid protein near the active site of recombinant ␤-galactosidases dramatically increased the enzyme responsiveness to specific antipeptide antibodies, including sera from infected animals (4,17). In this study, we report that recombinant ␤-galactosidases accommodating one or two different peptides from the FMDV NS protein 3B per enzyme monomer can be reactivated by anti-3B monoclonal antibodies (MAbs).…”
mentioning
confidence: 95%
“…We previously showed that multiple insertions of a major FMDV B-cell epitope from the VP1 capsid protein near the active site of recombinant ␤-galactosidases dramatically increased the enzyme responsiveness to specific antipeptide antibodies, including sera from infected animals (4,17). In this study, we report that recombinant ␤-galactosidases accommodating one or two different peptides from the FMDV NS protein 3B per enzyme monomer can be reactivated by anti-3B monoclonal antibodies (MAbs).…”
mentioning
confidence: 95%